cos (A + B)

cos (A + B)

How to solve cos (A + B) problems: formula, proof, example, and its solution.

Formula

cos (A + B) = cos A cos B - sin A sin B

cos (A + B) = cos A cos B - sin A sin B

Proof

cos (A + B): Proof of the Formula

cos (A + B) = cos (A - (-B))

Then cos (A - (-B)) = cos A cos (-B) + sin A sin (-B).

cos (-B) = cos B
sin (-B) = -sin B

Trigonometric functions of (-θ)

Example

Find the value of the given expression. cos 75 degrees

cos 75º = cos (30º + 45º)
= cos 30º cos 45º - sin 30º sin 45º

Draw a 30-60-90 triangle and a 45-45-90 triangle.

Cosine: CAH.
So cos 30º = √3/2.
And cos 45º = 1/√2.

Sine: SOH.
So sin 30º = 1/2.
And sin 45º = 1/√2.

So cos 30º cos 45º - sin 30º sin 45º
= (√3/2)⋅(1/√2) - (1/2)⋅(1/√2).

Rationalizing a denominator